2021
DOI: 10.3390/children8030212
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Review Exploring Psycho-Social Impacts and Therapeutic Interventions for Parent Caregivers of Young People Living with Duchenne’s Muscular Dystrophy

Abstract: The purpose of this integrative review was to explore psycho-social impacts and therapeutic interventions for parent caregivers of young people living with Duchenne’s Muscular Dystrophy (DMD). Electronic databases were searched for research publications between 2010 and 2020. This included Medline, CINAHL, PsycINFO, ERIC, ERC, and AMED. Four central themes emerged: Living with DMD; Knowing and telling; Transitioning; and Building resilience. The impact on parents caring for a child with DMD affected all aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…Another study found a higher degree of physical and emotional fatigue due to the work of "caring" for the dependent person is associated with a higher presence of cardiovascular somatic symptoms (22). It has been reported that parents of children with NMDs who had developed health problems (sleep problems, back problems and hypertension) were worried about not being as able to care for their child, which ultimately increased overload (4). Burnout syndrome can therefore be significantly influenced by individuals' cognitions and how they perceive themselves, i.e., whether they perceive themselves as being able to cope with caregiving tasks.…”
Section: Factors That Influence Caregiver Overloadmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study found a higher degree of physical and emotional fatigue due to the work of "caring" for the dependent person is associated with a higher presence of cardiovascular somatic symptoms (22). It has been reported that parents of children with NMDs who had developed health problems (sleep problems, back problems and hypertension) were worried about not being as able to care for their child, which ultimately increased overload (4). Burnout syndrome can therefore be significantly influenced by individuals' cognitions and how they perceive themselves, i.e., whether they perceive themselves as being able to cope with caregiving tasks.…”
Section: Factors That Influence Caregiver Overloadmentioning
confidence: 99%
“…Most NMDs are genetic and manifest clinically during childhood (3). All NMDs have in common the following symptoms that eventually lead to dependence in the patient: muscle weakness, musculoskeletal deformity and pain, deteriorating respiratory and cardiac function loss of ambulation, and fatigue (4,5). This results in a need for constant supervision and attention, thus most patients with NMDs live at home and receive daily assistance from family members, and the majority of them are usually parents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this study is international, the supportive programs are unique to each country and cannot be compared, as the number of resources available, government support, and disease frequency play a role in determining the administration of such programs. Thus, further exploring the availability and accessibility of support programs such as therapy will allow caregivers to prioritize their mental health and mitigate the negative impacts taking care of a patient with a terminal illness may induce (e.g., anxiety, depression) [ 10 , 12 ].…”
Section: Reviewmentioning
confidence: 99%
“…Duchenne muscular dystrophy (DMD) is a lethal X-linked disease characterized by progressive muscle wasting with high burden on patients and family members. 1 , 2 , 3 , 4 The prevalence is estimated to 19.8 per 100,000 live male births, 7.1 cases per 100,000 males, and 2.8 cases per 100,000 individuals in the general population. 5 The prevalence is also evaluated at 10.9, 6.1, 2.2, and 1.9 per 100,000 males respectively in France, Canada, the United Kingdom, and the United states.…”
Section: Introductionmentioning
confidence: 99%